2020
DOI: 10.1371/journal.pone.0236940
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and qualitative evaluation of a learning model based on workstation activities

Abstract: Background Moving towards a horizontal and vertical integrated curriculum, WorkStation Learning Activities (WSLA) were designed and implemented as a new learning instrument. Here, we aim to evaluate whether and how this specific learning model affects academic performance. To better understand how it is received by medical students, a mixed methods research study was conducted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…In summary, by permitting physical manipulation of material within the learning environment, we conclude that WSLA provides better understanding of the content and more effective retention and integration of new information in knowledge from lectures. These general student´s perceptions are supported by previous work published by our research group, as we described that students understand better those learning objectives associated with higher levels of cognitive learning in Bloom's taxonomy in the context of WSLA methodology [16].…”
Section: M5: 'I Really Like It Because It Helps Me Lock Down the Info...supporting
confidence: 84%
See 2 more Smart Citations
“…In summary, by permitting physical manipulation of material within the learning environment, we conclude that WSLA provides better understanding of the content and more effective retention and integration of new information in knowledge from lectures. These general student´s perceptions are supported by previous work published by our research group, as we described that students understand better those learning objectives associated with higher levels of cognitive learning in Bloom's taxonomy in the context of WSLA methodology [16].…”
Section: M5: 'I Really Like It Because It Helps Me Lock Down the Info...supporting
confidence: 84%
“…Very briefly, WSLA is organized around workstations, each one focusing students' work on concrete outcome(s) within the same clinical case. It follows five different steps which were described in detail by González-Soltero et al [16]. Over years of experience, we noted that these five steps can be operationally related with the different learning modes mentioned above:…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies have identified WSLA as an effective strategy to promote deep learning and improve academic performance in medical early years curricula [14,15]. Qualitative analysis suggests that students perceive WSLA as a motivating and constructive framework for understanding complex concepts, highlighting the role of Fig.…”
Section: Introductionmentioning
confidence: 91%
“…Various models of blended learning in higher education are currently widely represented in the literature [6], [7], [8], [9], [10], [11]. Most common are the following four models: Flipped learning or the flipped classroom, laboratory rotation, station rotation, and a flexible model [9], [11], [12], [13], [14].…”
Section: Introductionmentioning
confidence: 99%